2020
DOI: 10.1021/acs.nanolett.0c03141
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Mott–Hubbard Physics in Nanoparticle Solids: Transitions Driven by Disorder, Interactions, and Their Interplay

Abstract: We show that adapting the knowledge developed for the disordered Mott−Hubbard model to nanoparticle (NP) solids can deliver many very helpful new insights. We developed a hierarchical nanoparticle transport simulator (HINTS), which builds from localized states to describe the disorder-localized and Mott-localized phases of NP solids and the transitions out of these localized phases. We also studied the interplay between correlations and disorder in the corresponding multiorbital Hubbard model at and away from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Mobility simulations were performed utilizing the Hierarchical Nanoparticle Transport Simulator (HiNTS) kinetic Monte Carlo code, developed by some of us previously. 41,42 HiNTS simulates transport by developing several modeling layers and then integrating them into a hierarchical scheme. Aer the energetics of the individual QDs is computed by ab initio methods, the QD-to-QD transitions of the charges are described by the following two mechanisms:…”
Section: Mobility Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobility simulations were performed utilizing the Hierarchical Nanoparticle Transport Simulator (HiNTS) kinetic Monte Carlo code, developed by some of us previously. 41,42 HiNTS simulates transport by developing several modeling layers and then integrating them into a hierarchical scheme. Aer the energetics of the individual QDs is computed by ab initio methods, the QD-to-QD transitions of the charges are described by the following two mechanisms:…”
Section: Mobility Simulationmentioning
confidence: 99%
“…Based on our previous work, we chose the electron density to be 0.5 electrons per QD, remaining far from commensuration to avoid Coulomb blockade effects. 41 A small voltage of 1 mV was then applied across electrical contacts on opposite sides of each sample to induce electron transport. Periodic boundary conditions were used.…”
Section: Mobility Simulationmentioning
confidence: 99%
“…We expect that the cations produce a corrugated potential at the crystal/ionic liquid interface that may be disordered, or ordered, depending on the accumulated interfacial charge . This potential energy landscape will be pronounced for the smaller DEME and N4441 cations, and it seems reasonable that this potential, combined with the Hubbard electron–electron interaction, causes the strongly insulating state near 1 e/C 60 . , …”
Section: Resultsmentioning
confidence: 98%
“…44 This potential energy landscape will be pronounced for the smaller DEME and N4441 cations, and it seems reasonable that this potential, combined with the Hubbard electron−electron interaction, causes the strongly insulating state near 1 e/C 60 . 61,62 When the cation radius increases in the case of N8881-based EDLTs, the physical situation changes markedly. The mobility data indicate accumulated electrons are delocalized, and we suggest that this implies that the corrugation potential from the cations is now greatly diminished.…”
Section: Resultsmentioning
confidence: 99%
“…38, see also 39 Very recently, we demonstrated that NC solids are an excellent platform to study Mott-Hubbard phenomena, as they exhibit transport transitions driven by interactions, by disorder, and by their interplay. 40 In this paper, we adapt and apply our hierarchical transport simulator HINTS 35,38 to study charge transport in binary nanocrystal solids (BNSs) consisting of PbSe NCs of two different sizes. Our simulation results are motivated by early stage efforts to measure the transport of such binary NC films fabricated with layerby-layer dip coating of colloidal mixtures.…”
Section: Introductionmentioning
confidence: 99%